Surviving the past, coping with the present, hoping for a future of justice: the dispute resolution practices of the Marrons of Suriname. Issue 2 (3rd April 2017) - Velthuizen, Andreas
Abstract: This article set out to identify the dispute resolution practices that survived historic events such as slavery and colonialism that can add value to modern alternative dispute resolution (ADR) practices. A discussion on ADR and applying it to the African context set the framework for a discussion about the causal relationship between the ADR practices of the Marrons of Suriname and that of the Igbo of Nigeria. This relationship is explained in terms of the Atlantic slave trade and the customary dispute resolution practices of the Igbo. The ADR practices of the Marrons of Suriname are then explained. It was found that strong cohesiveness and kinship survived slavery, colonialism and serves as a value foundation to resolve disputes within a Marron community with a preference for mediation by the Elders and arbitration by leaders selected through customary processes. However, these practices are not yet part of modern jurisprudence and governance because it is not sufficiently codified or understood and accepted by people from outside the Marron culture.